Radiographic Reference Points Are Inaccurate With and Without a True Lateral Radiograph: The Importance of Anatomy in Medial Patellofemoral Ligament Reconstruction. (January 2016) - Ziegler, Connor G.; Fulkerson, John P.; Edgar, Cory
Background: Studies have reported methods for radiographically delineating medial patellofemoral ligament (MPFL) femoral tunnel position on a true lateral knee radiograph. However, obtaining a true lateral fluoroscopic radiograph intraoperatively can be challenging, rendering radiographic methods for tunnel positioning potentially inaccurate. Purpose: To quantify the magnitude of MPFL femoral tunnel malposition that occurs on true lateral and aberrant lateral knee radiographs when using a previously reported radiographic technique for MPFL femoral tunnel localization. Study Design: Descriptive laboratory study. Methods: Ten fresh-frozen cadaveric knees were dissected to expose the MPFL femoral insertion and surrounding medial knee anatomy. True lateral and aberrant lateral knee radiographs at 2.5°, 5°, and 10° off-axis were obtained with a standard mini C-arm in 4 orientations: anterior to posterior, posterior to anterior, caudal, and cephalad. A previously reported radiographic method for MPFL femoral localization was performed on all radiographs and compared in reference to the anatomic MPFL attachment center. Results: The radiographic point, as previously described, was a mean distance of 4.1 mm from the anatomic MPFL attachment on a true lateral knee radiograph. The distance between the anatomic MPFL attachment center and the radiographic point significantly increased on aberrant lateral knee radiographs with as little as 5° of rotational error in 3 of 4 orientations of rotation when a standard mini C-arm was used. This corresponded to a malposition of 7.5, 9.2, and 8.1 mm on 5°-aberrant radiographs in the anterior-posterior, posterior-anterior, and cephalad orientations, respectively ( P < .005). In the same 3 orientations of rotation, MPFL tunnel malposition on the femur exceeded 5 mm on 2.5° aberrant radiographs. Conclusion: The commonly utilized radiographic point, as previously described for MPFL femoral tunnel placement, results in inaccurate tunnel localization on a true lateral radiograph, and this inaccuracy is perpetuated with aberrant radiography. Aberrant lateral knee imaging of as little as 5° off-axis from true lateral has a significant effect on placement of a commonly used radiographic point relative to the anatomic MPFL femoral attachment center and results in nonanatomic MPFL tunnel placement. Clinical Relevance: This study demonstrates that radiographic localization of the MPFL femoral tunnel results in inaccurate tunnel placement on a true lateral radiograph, particularly when there is deviation from a true lateral fluoroscopic image, which can be difficult to obtain intraoperatively. Assessing anatomy directly intraoperatively, rather than relying solely on radiographs, may help avoid MPFL tunnel malposition.